The Erosion of Self: An Ethnographic Study of Women's Experience of Marriage to Alcoholic Husbands - Banister, Elizabeth M.; Vance Peavy, R. (Canadian Journal of Counselling and Psychotherapy, 2007)
An ethnographic study according to Spradley's (1979) Developmental Research Sequence (DRS) Method was conducted in order to develop knowledge about how women live out, interpret, and express the experience of living with an alcoholic husband. The discourses surrounding women whose husbands are alcoholic have been used to minimize women's experience. In addition, these same discourses have also contributed to the concept of codependency, an explanatory theme used in alcohol treatment programs and recent popular literature to dehne the wives' difficulties. In contrast, what stood out from this study is evidence of a complex interaction in the experience of women married to alcoholics involving internalization of cultural expectations, weakening of self, and embeddedness in an alcohol-dependent marriage. Suggestions for counsellors include consideration of how internalization of cultural norms and the interactional dynamics of the marital relationship seriously affect the women's experience. Further, ethnographic questions could be employed therapeutically to map out clients' meaning constructs and to develop a coherent understanding of clients' worlds. Finally, ethnographic questioning could be integrated into counsellor training programs to raise trainees' awareness of the significance of their clients' use of language.